Effect of sintering temperature on microstructure of TiZr alloy fabricated via powder metallurgy for biomedical applications - Kaya, Mehmet; Cakmak, Omer; Akkus, Abdurrahman; Annac, Ebru Elibol; Kom, Mustafa (Springer Heidelberg, 2025)
With the growing demand for advanced biomaterials, titanium-based alloys have garnered considerable attention, particularly Ti-Zr alloys due to their superior mechanical strength, excellent biocompatibility, and notably, their enhanced corrosion resistance within physiological environments. In this study, a Ti-20 at% Zr alloy was synthesized using the powder metallurgy technique for potential biomedical use. The influence of compaction pressure and sintering temperature on the alloy's porosity and microstructure was systematically analyzed through X-ray diffraction (XRD) and scanning electron microscopy (SEM). The alloy microstructure predominantly exhibited two distinct phases, denoted as alpha and alpha '. Additionally, crystal lattice parameters, grain size and micro-stresses were calculated using XRD peaks. It was understood that sintering temperature reduces micro-stresses by expanding the grain volume. Furthermore, electrochemical corrosion testing was conducted to evaluate the alloy's corrosion performance, and in vivo biocompatibility assessments were performed using a rat model. Findings revealed that increasing the compaction pressure and sintering temperature led to a reduction in porosity. Overall, the Ti-20 at% Zr alloy demonstrated promising bioactivity, remarkable biocompatibility, and robust resistance to corrosion, underscoring its suitability for biomedical applications.
Keywords: Ti-Zr alloy; Powder metallurgy; Microstructure analysis; Biomedical materials